APPROACHING LOCAL ELEMENT AND SUSTAINABILITY PRINCIPLES IN THE DESIGN PROCESS OF LOMBOK INTERNATIONAL AIRPORT WITH SENSE OF LOMBOK THEME - novrizal primayudha; Andika Dwicahyo Aribowo (Ide dan Dialog Desain Indonesia (Idealog), 2022)
Lombok International Airport has been expanded due to the increasing demand for peak hours for domestic and international passengers. The expansion is carried out by adding the east andwest sides by considering the concept of unity with the old building as well as local principles. Therefore, the design at this airport applies the principles and characteristics of Lombok which are considered as the basis for the "Sense of Lombok" theme, including the face of Indonesia, strongbuilding characters, local, sustainable, and iconic characters. The purpose of this research is toproduce a building and interior design for the expansion of Lombok Airport that applies the Sense of Lombok theme through architectural forms that elevate the shape of the facade and roof, as well as from the interior side with a sustainability approach and a more modern local character. The methodin this research consists of 3 main processes, namely Identification, Design Analysis, and DesignImplementation. The design process is carried out with a design awareness approach based on the theory developed by Mark Decay. Keywords : Airport, Lombok, Architecture, Interior, Sustainability